2015
DOI: 10.1007/s40596-015-0332-y
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Examination of Integrated Care in Undergraduate Medical Education

Abstract: Integration of behavioral and physical health in medical education is beginning to occur in a meaningful context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…health are currently integrated in medical school curricula. 8 As a result, there is incomplete understanding of how medical students can best learn the skills necessary to incorporate behavioral health interventions into clinical practice. In addition, prior research demonstrates that the values of clerkship directors can influence the curriculum that they deliver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…health are currently integrated in medical school curricula. 8 As a result, there is incomplete understanding of how medical students can best learn the skills necessary to incorporate behavioral health interventions into clinical practice. In addition, prior research demonstrates that the values of clerkship directors can influence the curriculum that they deliver.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that behavioral health topics are more likely taught during the family medicine clerkship than any other clinical rotation other than psychiatry. 8 Moreover, most mental health symptomatology presents first at the primary care level, so this care, and therefore training, needs to be integrated into primary care education.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In this issue, we present six papers on the theme of integrated care, including three empirical reports, a review, an example curriculum, and a systematic review [4][5][6][7][8][9]. Recently, the American Psychiatric Association also published a task force report on integrated care [10].…”
mentioning
confidence: 99%
“…Although the response rates were low, a majority of respondents offered integrated care rotations and electives and fewer than half of responding programs provided didactic education on integrated care. Dubé et al [5] surveyed members of the Association of Directors of Medical Student Education in Psychiatry (ADMSEP) on how physical and behavioral health were integrated at their institutions. Although response rates were again low, behavioral health was most commonly taught in courses dealing with the practice of medicine, in neurology and in reproduction courses, and in family practice clinics.…”
mentioning
confidence: 99%
See 1 more Smart Citation